Assessment of the Role of Hepatitis C Virus in the Pathogenesis of Hodgkin Lymphoma Patients - Bajwa, Hajra; Rafique, Iqra; Mehmood, Qaisar; Khan, Muhammad Hadi; Jamil, Hafsa; Zafar, Qasim (Indus Journal of Bioscience Research, 2025)
Background and Aim: Hepatitis C is a viral infection that mainly affects the liver, causing inflammation. Infection with hepatitis C virus (HCV) commonly observed and associated with various clinical manifestations, including a diagnosis in patients with B-cell Hodgkin lymphoma. Worldwide, HCV infection accounts for about 3% of the population and a major cause of chronic liver disease. The study was conducted to investigate the possible role of Hepatitis C virus (HCV) in the development and progress of Hodgkin Lymphoma. Patients and Methods: This cross-sectional study investigated 160 Hodgkin lymphoma patients in the department of Medicine of Mayo Hospital, Lahore from January 2024 to December 2024. All patients made a detailed clinical evaluation including taking history, physical examination and relevant laboratory examination. Diagnostic workup included full blood calculation (CBC), liver and kidney function test, B 2-microglobulin level, erythrocyte sedimentation rate (ESR), serum uric acid and serum lactate dehydrogenase (LDH). Abdominal ultrasonography demonstrated to assess lymphadenopathy and organomegaly. For staging and diagnosis, Tomography (CT), Bone Marrow Biopsy, and Polymerase Chain Reaction (PCR) conducted hepatitis C virus (HCV) contrast-comprehensive calculation for RNA. The presence of HCV infection confirmed by the enzyme immunosorbent assay (ELISA) and PCR techniques. Data analysis done using SPSS version 28. Results: A total of 160 patients diagnosed with Hodgkin lymphoma were nominated in the study, including 86 (53.8%) male and 74 [46.2%%] women, whose average age 46.6±9.6 years with an age range 16-65 years. Hepatitis C virus (HCV) infection was detected in 78 (48.8%), as confirmed by ELISA and PCR. Patients with HCV positivity showed high frequency of advanced-phase (Phase III/IV) compared to HCV-negative patients (P = 0.03). The level of elevated liver enzymes, serum LDH, and B2-microglobulin was quite popular among HCV positive HL cases (P <0.05). Statistical analysis indicated a significant relationship between HCV infection and aggressive disease features, suggesting the possible role of HCV in Hodgkin lymphoma's pathogenesis and clinical progression. Conclusion: The present study suggests a potential association between HCV infection and pathogenesis of Hodgkin lymphoma. HCV-positive patient has demonstrated more aggressive disease characteristics, including advanced phase, elevated inflammatory markers, and increased external participation. These results highlight the importance of regular HCV screening in HL patients and suggest that HCV may contribute to the progression of the disease.